Representation of Terrorism in 22 July Movie (John Fiske Semiotic Analysis) - Luthfi Fathullah; Indah Wenerda (Jurnal Indonesia Sosial Teknologi, 2024)
Paul Greengrass' 22 July depicts the tragic events of the July 22, 2011 terrorist attack in Norway. This research aims to describe the representation of terrorism in the movie "July 22". The qualitative method is used in this research. The data contained in this research are in the form of scenes that indicate acts of terrorism in the movie "22 July". The data were analysed using John Fiske's semiotic analysis technique, which consists of three levels: level of reality, level of representation, and level of ideology. The result of the research shows that the movie "22 July" contains elements of terrorism committed by Anders Behring Breivik. At the level of reality, the elements of terrorism are represented through aspects of costume, behaviour, expression, and conversation. At the level of representation, there are aspects of camera, lighting, and sound. At the ideological level, this movie represents the ideology of terrorism.